The characteristics of episodic migraine vs. chronic migraine at high altitude and the relationship with body mass index, education level and MIDAS (Annals of Medical Research, 2021)
None
Keywords: key, migraine prevalence was reported to be 16.4%. It was determined that chronic migraine (CM) accounts for 10.8% of overall migraine cases. Some studies alleged that migraine is more prevalent at high altitudes. Furthermore, a relationship has been reported between CM and body mass index (BMI) and education level. We investigated the characteristic features of migraine and their effects on the activities of daily living, as well as the body mass index and sociodemographic characteristics of the patients, who have been diagnosed with migraine in our outpatient clinic in the city center of Erzurum, which is located nearly 2,000 meters above the sea level.br /Material and Methods: Characteristics of migraine, sociodemographic data, body mass index and MIDAS scoresof 1347 patients aged 18-45 years, who have been living in the city center of Erzurum and have been diagnosed with migraine based on the ICHD-2 in neurology outpatient clinic between December 2012 and October 2015, were retrospectively evaluated. Patients were divided into two groups as episodic and chronic migraine.br /Results: Of the patients, the mean age was 30.4 (±8.4) years, 81.8% (n=1104) were female, and 32.3% (n=435) had chronic migraine. Statistically significant differences were observed between the two groups in terms of education level, MIDAS scores and BMI (p0.005).br /Conclusion: We detected high CM prevalence in such high altitude. Characteristic features of the disease were consistent with the literature. The rate of illiterate patients was higher in the CM group. The prevalence of CM increased with BMI. CM group had higher MIDAS scores. We think that high altitude, as well as BMI and education level, contributes to the disease to become chronic.br / Migraine; MIDAS; High altitude; Body Mass Index.